PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA SERTA DAMPAKNYA TERHADAP PRODUKTIVITAS KERJA PADA DIREKTORAT OPERASI DAN PRODUKSI KOMPARTEMEN OPERASI, UNIT KERJA AMMONIA PUSRI 2B - Pratama, Tri Gustrian; Nasir, Nasir; Veybitha, Yolanda (Forum Bisnis Kewirausahaan, 2024)
This research aims to determine and prove the influence of compensation and work environment on work motivation and its impact on work productivity, both directly and indirectly. The population in this study were employees of the Operations and Production Directorate of the Operations Compartment, Pusri 2B Ammonia Work Unit, totaling 87 people. namely 87 employees. The data analysis used in this research is using the Structural Equation Model (SEM) analysis method which is operated through the Partial Least Square (PLS) program. The results of this research show that the Compensation variable influences Work Motivation, the Work Environment variable influences Work Motivation, the Compensation variable influences Work Productivity, the Work Environment variable influences Employee Work Productivity, the Work Motivation variable influences Employee Work Productivity, the Compensation variable influences Productivity Work has an indirect influence with Work Motivation as a mediating variable, the Work Environment variable on Work Productivity has an indirect influence with Work Motivation as a mediating variable. The R2 value for the latent variable Work Motivation as a mediating variable is 0.949, which means that this value identifies that variations in Employee Work Motivation can be explained by exogenous latent variables (Compensation and Work Environment) amounting to 94.9% while the remaining 5.1% is explained by variables other. The R2 value for the latent variable Work Productivity is 0.939, which means that this value identifies that variations in Work Productivity can be explained by exogenous variables (Compensation, Work Environment and Work Motivation) amounting to 93.9% while the remaining 6.1% is explained by variables that are not present. in research.